2022
DOI: 10.3389/fpubh.2021.812737
|View full text |Cite
|
Sign up to set email alerts
|

Serial-Multiple Mediation of Job Burnout and Fatigue in the Relationship Between Sickness Presenteeism and Productivity Loss in Nurses: A Multicenter Cross-Sectional Study

Abstract: Background:In China, sickness presenteeism, job burnout, and fatigue are common among nurses during the COVID-19 pandemic. We propose the prevalence of sickness presenteeism can adversely affect nurses' physical and mental health, negatively impact their work productivity and quality, and pose a threat to patients' safety. Therefore, this study examines the mechanism of productivity loss caused by sickness presenteeism, fatigue, and job burnout.Objectives:To investigate the serial-multiple mediating effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 45 publications
0
23
0
Order By: Relevance
“…Hence, the workplace environment has a substantial role in determining the mental health (as well physical health) of the working adults. Earlier reports confirm the compromise in occupational mental health and presence of psychological hazards in the workplace environment leads to economic loss by direct (e.g., absence, retirement) as well indirect loss (such as compromise in the quality of life, subnormal productivity) to the worker and the employer 2,3) . Burnout, is a psychological syndrome involving exhaustion of emotional resources, depleted compassion / empathy to fellow individuals (depersonalization / cynicism) and a perception of incompetence and lack of achievement / adequate productivity at work (personal accomplishment) as a consequence of extended exposure to psychological hazards (occupational stress) at work environment 4) .…”
Section: Introductionmentioning
confidence: 85%
“…Hence, the workplace environment has a substantial role in determining the mental health (as well physical health) of the working adults. Earlier reports confirm the compromise in occupational mental health and presence of psychological hazards in the workplace environment leads to economic loss by direct (e.g., absence, retirement) as well indirect loss (such as compromise in the quality of life, subnormal productivity) to the worker and the employer 2,3) . Burnout, is a psychological syndrome involving exhaustion of emotional resources, depleted compassion / empathy to fellow individuals (depersonalization / cynicism) and a perception of incompetence and lack of achievement / adequate productivity at work (personal accomplishment) as a consequence of extended exposure to psychological hazards (occupational stress) at work environment 4) .…”
Section: Introductionmentioning
confidence: 85%
“…Research, past and present, supports the relationship between nurses’ occupational stress and poor mental and physical health, and less than optimal well-being, for nurses, patients, and health care institutions (Aiken et al, 2001, 2002; Gershon et al, 2007; Gartner et al, 2010; Li et al, 2022; Vasconcelos et al, 2016; Vandenbroeck et al, 2017). Research also supports the relationship between HT and stress reduction for both those who give and receive the treatment (Tang et al, 2010; Anderson et al, 2017), yet there is a lack of randomized studies exploring nurses use of HT during a work shift in an acute care hospital, to alleviate stress and promote nurses’ self-care.…”
Section: Background and Significancementioning
confidence: 97%
“…A landmark study investigating mortality patterns of nurses found that nurses are more likely to die before the age of 65 years than other occupations in that same time period (Peipins et al, 1997). Studies in the same frame supported these findings (Ader et al, 1991;Aiken et al, 2001) and began correlating elevated levels of nurses' stress with mental illnesses such as depression, anxiety, and decreased well-being (Aikin et al, 2008;Li et al, 2022). Subsequent systematic and integrative reviews correlated nurses' elevated stress perception with nurses' physical and mental health resulting in poor quality of patient care and increased rates of nurse sick days and turnover, (Adams et al, 2019;Letvak et al, 2012) resulting in significant financial loss for health care institutions (Halter et al, 2017;Roberts et al, 2012).…”
Section: Nursing Stressmentioning
confidence: 99%
“…Other recognized determinants of absenteeism in HCW include organizational aspects, inadequate working conditions, long hours, task overload, interpersonal con icts, low autonomy and remuneration, associated with psychological, cognitive and physical professional overload (213), all aggravated during a PHEIC. Sometimes, HCW might opt to work even if not feeling well, a practice known as sickness presenteeism which as deleterious effects such as increased risk of burnout or loss of productivity (211,214). Leaving or intention to leave the occupation emerged as a relevant impact of PHEICs (215,216).…”
Section: Resultsmentioning
confidence: 99%